Nonhost neighborhood increases biocontrol weevil damage to the nontarget, federally threatened Pitcher's thistle (Cirsium pitcheri) - Alyssa S. Hakes; Zechariah D. Meunier (Global Ecology and Conservation, 2018)
Studies that monitor the intensity of biocontrol insect damage on target and nontarget hosts in the field often consider the effects of neighboring vegetation that serve as acceptable alternative hosts. Whether nonhost neighboring plants can also influence damage to hosts has received less attention. The nonnative, seed-eating weevil Larinus planus has been distributed as a biocontrol agent for weedy thistles in the U.S., but also attacks native thistles including the federally threatened Cirsium pitcheri. To test the hypothesis that nonhost Ammophila breviligulata grass neighbors increase susceptibility of C. pitcheri to L. planus damage, we clipped the neighboring vegetation within a 1 m radius around focal C. pitcheri, and assessed weevil infestation in flower heads of plants with clipped or unclipped neighbors. We also examined elevational effects by surveying weevil presence along an environmental gradient and comparing infestation rates between primary and secondary dune habitats with intact neighboring vegetation. Larinus planus infestation was more prevalent at low than at high dune elevations. At low elevations, clipping neighboring vegetation surrounding C. pitcheri significantly decreased the proportion of flower heads infested by weevils. Grasses may aid L. planus dispersal to C. pitcheri hosts and/or provide a refuge from environmental stress or natural enemies. Our results highlight two factors that predict L. planus attack, as well as areas of the dune on which to focus Cirsium pitcheri management or weevil control efforts. More broadly, our results suggest that nonhost neighboring vegetation may be an important factor determining the intensity of damage by invasive and biocontrol insects. Keywords: Associational susceptibility, Elevation, Invasive species, Larinus planus